2013
DOI: 10.1167/13.14.7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-based heuristics for material perception

Abstract: People often make rapid visual judgments of the properties of surfaces they are going to walk on or touch. How do they do this when the interactions of illumination geometry with 3-D material structure and object shape result in images that inverse optics algorithms cannot resolve without externally imposed constraints? A possibly effective strategy would be to use heuristics based on information that can be gleaned rapidly from retinal images. By using perceptual scaling of a large sample of images, combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 66 publications
7
34
0
Order By: Relevance
“…We find that this indeed allows the user to adjust different aspects of the proximal image. For highlights, many authors have already shown how their specific characteristics influence perception of glossiness (see e.g., Anderson, 2011;Giesel & Zaidi, 2013;Motoyoshi et al, 2007). Perception of velvetiness, glitter, and sparkle concern undeveloped topics.…”
Section: Discussionmentioning
confidence: 99%
“…We find that this indeed allows the user to adjust different aspects of the proximal image. For highlights, many authors have already shown how their specific characteristics influence perception of glossiness (see e.g., Anderson, 2011;Giesel & Zaidi, 2013;Motoyoshi et al, 2007). Perception of velvetiness, glitter, and sparkle concern undeveloped topics.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that at least some material properties are characterized by specific spatial-frequency components of the surface (Bex & Makous, 2002;Giesel & Zaidi, 2013). For example, Giesel and Zaidi (2013) showed that the apparent water absorbency of a surface could be related to the apparent thickness of the surface, and that the apparent thickness in turn could be modulated by changing the relative energy of the frequency band of 8-15 c/image. This band is close to the 6-24 c/image that was shown to be a critical band for producing the stain-on-texture phenomenon in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…By user studies, Giesel and Zaidi found a relation between certain affordances or material properties and spatial frequency bands in material-images [11]: 0.57-2.29 c/°Inflated and deflated 2. 29-4.28 c/°Deep and flat 6.57-15.14 c/°Soft and rough 15.14-19.42 c/°Sparkling and dull The connection between affordance and spatialfrequencies gives rise to a semantically founded editing scheme by simply enhancing or weakening particular frequency bands [12,29]. Because the underlying physical effects are too complicated, those effects may not be seen as the result of inverse optics [12] and are therefore examples for complex physical operations with a linear representation in the visual cortex.…”
Section: Bandpass Filteringmentioning
confidence: 99%
“…29-4.28 c/°Deep and flat 6.57-15.14 c/°Soft and rough 15.14-19.42 c/°Sparkling and dull The connection between affordance and spatialfrequencies gives rise to a semantically founded editing scheme by simply enhancing or weakening particular frequency bands [12,29]. Because the underlying physical effects are too complicated, those effects may not be seen as the result of inverse optics [12] and are therefore examples for complex physical operations with a linear representation in the visual cortex. It is striking, that those manipulations cover nearly the whole frequency range of the visual cortex (figure 4).…”
Section: Bandpass Filteringmentioning
confidence: 99%
See 1 more Smart Citation